Relationship between night-sleep duration and risk for depression among middle-aged and older people: A dose–response meta-analysis - Li, Xin-lin; Wei, Jiayin; Zhang, Xinying; Meng, Zhuo; Zhu, Wentao (Frontiers in Physiology, 2023)
Objective: To examine the dose-response associations between night-sleep duration and depression risk in middle-aged and elderly adults. Methods: We searched Pubmed, Embase, Web of science, CNKI, VIP, Wanfang data knowledge service platform, from inception to 31st July 2022. Cohort and case-control studies assessing night-sleep duration with depression were adopted. We used the Newcastle –Ottawa scale (NOS) to assess the quality of the published researches. Two researchers carried out data exaction and quality assessment respectively. Restricted cubic spline function and generalized least squares method would be used to establish dose-response relationships between sleep duration and depression. We aimed to analyze the estimated effect size presented as the risk ratio (RR) and its 95% confidence interval (CI) using Stata 12.0. Result: Six cohort studies with 33595 participants were included in this meta-analysis. A U-shaped association between sleep duration and depression risk was revealed. On one hand, compared with seven-hour night-sleep, both shorter and longer sleep duration were associated with increased risk of depression (5 hours: RR = 1.09, 95% CI =1.07–1.12; 6 hours: RR = 1.03, 95% CI = 1.02–1.04; 8 hours: RR = 1.10, 95% CI =1.05–1.15; 9 hours: RR = 1.31, 95% CI = 1.17–1.47; 10 hours: RR = 1.59, 95% CI = 1.31–1.92; non-linear test P＜0.05). On the other, increased risk of depression with shorter sleep duration was observed in middle-aged and elderly people among non-Asian population (5 hours: RR = 1.09; 95% CI = 1.02–1.17), while both shorter and longer sleep duration can increase the risk of depression among Asian population (5 hours: RR = 1.10, 95% CI = 1.07–1.13; 6 hours: RR = 1.04, 95% CI = 1.02–1.05; 8 hours: RR = 1.09, 95% CI = 1.05–1.14; 9 hours: RR = 1.35, 95% CI = 1.18–1.53; 10 hours: RR=1.70, 95%CI=1.36–2.12). Conclusion: The lowest-risk onset of depression occurred among middle-aged and elderly people with seven-hour night sleep, which suggested that shorter and longer night-sleep duration might lead to an increased incidence of depression. Keywords: night-sleep duration, sleep duration, depression, dose-response relation, meta-analyses.